2020
DOI: 10.1002/jbm.b.34630
|View full text |Cite
|
Sign up to set email alerts
|

Study on the osteogenesis of rat mesenchymal stem cells and the long‐term antibacterial activity of Staphylococcus epidermidis on the surface of silver‐rich TiN/Ag modified titanium alloy

Abstract: The main causes of failure of orthopedic implants are infection and poor bone ingrowth. Surface modification of the implants to allow for long‐term antibacterial and osteogenic functions is an effective solution to prevent failure of the implants. We developed silver‐rich TiN/Ag nano‐multilayers on the surface of titanium alloy with different doses of Ag+. The antibacterial stability and osteogenesis of the silver‐rich surface were determined by evaluating the adhesion and proliferation of Staphylococcus epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…36 Electrochemical surface treatment 37 or application of an antibacterial material coatings have been also employed to reduce bacterial adhesion. 8 Recently, several studies have exhibited an increased antibacterial activity of GO. [40][41][42] A previous study by Liu and Qiu 42,43 reported that treating surfaces with GO promoted antibiotic effects and bone activation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36 Electrochemical surface treatment 37 or application of an antibacterial material coatings have been also employed to reduce bacterial adhesion. 8 Recently, several studies have exhibited an increased antibacterial activity of GO. [40][41][42] A previous study by Liu and Qiu 42,43 reported that treating surfaces with GO promoted antibiotic effects and bone activation.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies attempted to coat on titanium with ZrN or Ag nanos, which is known to have antibacterial effects, and applied it to the implant abutments. 8,[60][61][62] In addition, some studies suggested that bacteria living at the interface of implant abutment and prosthesis could be prevented. 63 Carinci et al 64 examined bacterial viability and biofilm formation on the inside of implants coated with chlorhexidine and reported that soft tissues were effectively healed without any inflammatory symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abovementioned studies show that PAN-based materials might represent a potential candidate for bone-integrating orthopedic implants. Currently, poor formation of bounding at the interface between bone implant and infection represents a challenge in maintaining implant survival [27]. Modifying the biological response improves biocompatibility and integration with adjacent bone tissue on the orthopedic implant surface.…”
Section: In Vivo Evaluation Of Infected Wound Mouse Modelmentioning
confidence: 99%
“…43 Other approaches, such as adding a silver coating to a material, can reduce bacterial attachment but the high doses required to kill pathogens also reduce osteoblast activity. 44 Topographical approaches offer another interesting way to address this problem. One approach has been to mimic the bactericidal, high aspect ratio topographies that are present on insect wings, such as on Clanger cicada (Psaltoda claripennis) 45 and the dragonfly (Diplacodes bipunctata) 46 .…”
mentioning
confidence: 99%